An ANALYSIS PERSONIFICATION IN ALL THINGS BRIGHT AND BEAUTIFUL SELECTED SONGS - Putri, Adelya (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
Abstract This article is entitled An Analysis of Personification in All Things Bright and Beautiful Selected Song. The aims to classified type of personification in All Things Bright and Beautiful selected songs and their meanings. The theory are used for this research from Kennedy (1995:677) to analyze the type of personification from the lyrics in the songs, such as: Alligator Sky, Plant Life, Angels, The Real World which lyrics contain with personification in the lyrics. Meanwhile, to describe the meaning contained in the lyrics of the song, this research used theory meaning from Leech (1981:5-9) and used descriptive qualitative method based from situation. In this study used a table to describe the classification of the data that were analyzed. After classifying the data according to the type of personification and the meanings obtained, tit continue by concluding the meaning of lyrics in each selected song: Alligator Sky, Plant Life, Angels, The Real World. There are several lyrics containing Personification found, based on the theory from Kennedy (1995:677) but there were only found 4 types of meaning from 7 types meaning based on the theory of Leech (1981:5-9) they are affective meaning and reflected meaning.